Clinico-etiological profile of hospitalized paediatric patients: COVID-19 and non-COVID-19 in a district hospital of Northern India during lockdown period - Kaur, Ramanjot; Pandit, Sadbhavna; Dhawan, Neeraj (International Journal of Contemporary Pediatrics, 2021)
Background: With the sudden outbreak of coronavirus pandemic in 2020, there is a paucity of data on the clinical and epidemiological profile of COVID positive paediatric patients. Objective of the study was a retrospective analysis of both COVID-19 and non-COVID-19 cases admitted to a district Hospital of Northern India. Methods: A retrospective cross-sectional study was conducted in the Pediatric Emergency Department of Government Multi-speciality Hospital, Chandigarh from 22 March 2020 till 30 November 2020. Results: A total of 842 children were enrolled. Among neonates, 33% had sepsis as the major admitting diagnosis and SARI in children less than 1 year (excluding neonates) (33.5%) and in the 1-5 years age group (37.3%). In children more than 5 years, acute febrile illnesses were the main admitting diagnosis (50.4%). 204 patients (24.2%) were tested for COVID-19. 62 children (30.4%) were found to be positive. Asymptomatic children (74.2%) dominated the COVID-19 positive group. The most common symptom included fever (87.5%) with no reported mortality. Atypical symptoms (56.1%) were more common than respiratory symptoms. The majority of children had mild COVID-19 symptoms (62.6%). The unusual presentation of COVID-19 was in the form of acute appendicitis (6.2%) and renal vein thrombosis (6.2%) in the symptomatic group. Conclusions: For children with COVID-19, most of them were infected via family clustering, were asymptomatic, and had mild symptoms with an overall good prognosis. However, for atypical cases, a high suspicion of COVID-19 associated multisystem inflammatory syndrome should be kept in mind for early diagnosis.